PENILAIAN KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN ANALISIS RASIO KEUANGAN (Studi Pada Perusahaan Semen Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2013-2016) - YULIANA, RISKA INTAN (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Indonesia is a country with high population and high population growth. Along with the increase of the population does the demand for cement increase. Therefore, assessment on the financial performance of Indonesian cement companies is required. This study measures company performance using financial ratio analysis. The population of this study is cement companies listed in the Indonesia Stock Exchange during the period of 2013-2016. The sample of this study is PT. Indocement Tunggal Prakarsa Tbk, PT. Semen Indonesia, and PT. Holcim Indonesia Tbk. The ratios used in this study are liquidity, solvability, profitability, and activity ratio.The results of this study show that the liquidity, solvability, and profitability ratio of PT. Holcim Indonesia Tbk are the lowest, but its activity ratio is the highest of the three companies.Keywords: cement companies, financial performance, financial ratio, liquidity, solvability, profitability, activity.